A comparative analysis of professionally oriented opinion-sharing dialogue and discussion in teaching English to future power engineers - Shevchenko, Mariana (ScienceRise: Pedagogical Education, 2026)
The article presents the results of a thorough theoretical and methodological study devoted to the functional and structural differentiation between two key types of professional spoken interaction: professionally oriented opinion-sharing dialogue and professionally oriented discussion. The methodological need to implement professionally oriented opinion-sharing dialogue training in English for Specific Purposes (ESP) lessons for third-year undergraduate students in power engineering specialities is substantiated by the transition to the study of highly specialised disciplines and the need to prepare future professionals for international engineering cooperation in the energy sector. The work proposes a systematic comparison between professionally oriented opinion-sharing dialogue and professionally oriented discussion based on 20 parameters that cover functional, structural, psychological, and ethical aspects of professional oral communication. Attention is also paid to the features of implementing these types of dialogue in distance and blended learning formats, which have become popular in modern higher education institutions worldwide. It has been identified that professionally oriented opinion-sharing dialogue is a fundamental cognitive tool for the collaborative development of innovative technologies and engineering projects, modernisation of power systems, and coordination of technical work within a globalised professional environment. A comparative analysis of the parameters proposed in the present article reveals that professionally oriented opinion-sharing dialogue is a flexible, cooperative interaction characterised by spontaneous exchange, indirect disagreement, and the pursuit of shared consensus without requiring a facilitator. Conversely, professionally oriented discussion is a strictly regulated, competitive debate necessitating a facilitator, prepared argumentation, and rigid turn-taking to establish the superiority of a single perspective. The results of the study enable ESP lecturers to more accurately differentiate methodological tools and create exercises that meet the real demands of the modern energy industry. It has been proven that incorporating such approaches contributes to the holistic development of professional foreign-language (English) communicative competence in students at technical faculties. The paper’s practical value lies in the possibility of using the developed criteria to create innovative educational materials (potentially) based on authentic videos in English, i.e. thematically relevant movies and programmes, to develop the professional English spoken interaction skills of the mentioned students. This will enable the educational process to closely mirror the real conditions of international professional communication, thereby enhancing the readiness of future power engineers to solve professional tasks